Back-end-of-line compatible Hf0.5Zr0.5O2 ferroelectric devices enabled by microwave annealing - Yinchi Liu; Hao Zhang; Jining Yang; Dmitriy Anatolyevich Golosov; Xiaohan Wu; Chenjie Gu; Shijin Ding; Wenjun Liu (Chip)
In this work, we demonstrate an extremely low annealing processing at 300 °C for the crystallization of Hf0.5Zr0.5O2 (HZO) films with the adoption of microwave annealing (MWA). Compared to conventional annealing methods, an enhanced double remnant polarization (2Pr) of 55.4 μC/cm2, a higher maximum dielectric constant, and nearly wakeup-free were realized by modulating the power of the microwave. It is believed that the increasing loss factor of zirconia with rising temperature allows more energy to be extracted from the microwave and transferred to the ferroelectric HZO molecules, which facilitates the crystallization at low temperature. Furthermore, an amorphous indium gallium zinc oxide ferroelectric field-effect transistor treated with microwave annealing was fabricated, and a competitive memory window of 1.5 V was substantially achieved. These findings offer insights into the integration of HfO2 ferroelectric materials in non-volatile memory devices compatible with back-end-of-line (BEOL) in the future.